2006
DOI: 10.1002/adma.200600154
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐Mediated Generation of Iso‐Oriented Dense and Mesoporous Crystalline Metal‐Oxide Layers

Abstract: The fabrication of thin layers of a transition-metal oxide with 3D oriented crystallites has substantial importance for industrial applications, for example, semiconductor technology. [1,2] Chemical vapor deposition [3] and molecular beam epitaxy [4] onto single-crystalline substrates are widely used fabrication techniques but they suffer from elaborate preparation setups. Most of the currently applied concepts to generate layers of oriented crystals involve the deposition of molecular species from the gas pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 25 publications
(25 reference statements)
6
64
0
Order By: Relevance
“…[22] This is due, in part, to the fact that the synthesis of non-silicate oxides with both a well defined pore-solid architecture and highly crystalline walls itself is still challenging. One of the reasons for this is the lack of appropriate polymer SDAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] This is due, in part, to the fact that the synthesis of non-silicate oxides with both a well defined pore-solid architecture and highly crystalline walls itself is still challenging. One of the reasons for this is the lack of appropriate polymer SDAs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we take advantage of the superior templating properties of poly(ethylene-co-butylene)-block-poly(ethylene oxide) -referred to as KLE [22,25,27,31] -and polyisobutylene-block-poly(ethylene oxide) -referred to as PIB x -b-PEO y [32] -diblock copolymers to achieve thermally stable, high quality nanomaterials with tailorable pore and grain sizes. Overall, it seems that the unique combination of nanoscale porosity with crystalline texture might offer the possibility to broaden the scope of application for these oxide ceramics.…”
mentioning
confidence: 99%
“…Brezesinski et al have recently reported the oriented growth of oxides assisted by surfactants. [18] These insights can explain the fact that oriented growth of rutile is observed for the mesoporous film, while no remarkable oriented growth of titania can be discerned in the nonporous film ( Figure 3). [18] Notably, the onset of crystallization (observable by WAXS) is higher than the decomposition temperature.…”
Section: à3mentioning
confidence: 96%
“…[18] These insights can explain the fact that oriented growth of rutile is observed for the mesoporous film, while no remarkable oriented growth of titania can be discerned in the nonporous film ( Figure 3). [18] Notably, the onset of crystallization (observable by WAXS) is higher than the decomposition temperature. We speculate that at lower temperatures oriented crystallization occurs at the interface to www.chemphyschem.org the substrate, which is not detectable by WAXS due to the very low quantities of material at the interface.…”
Section: à3mentioning
confidence: 96%
See 1 more Smart Citation